KAJIAN TERJEMAHAN PENANDA KOHESI PRONOMINA DAN IDEOLOGI PENERJEMAHAN PADA HADITS ARBA'IN KE 31-40 KARYA IBNU DAQIQ AL 'IED KE DALAM BAHASA INDONESIA - Qonitatul Mahmudah; Ramiz Ansharil Haq; Muhammad Ridwan (Haluan Sastra Budaya, 2017)
Hadith Arba’in is a collection of the selected 42 hadiths. The name of Arba’in is taken from the amount of hadiths included in the book which is 42 hadiths. The book of hadith Arba’inis considered to be necessarily studied because this book contains the collection of the well know hadiths in islamic community awund the world. This book contains the main hadith that are very important in islamic study, started with hadith about the intention to start doing something, then followed with the basic aqidah, syari’ah, akhlak, and prophet’s advice. This research specifically studies the hadiths from 31-40 because they contain suggestion, forbiddence, excellence, and some of advices about islam. This research is descriptive qualitative research. The method used is (equal/comparison) method. The data in this research are grammatical cohesion marker in the form of pronoun in Arabic language and ideological translation in the 31-40 text of hadith Arba’in written by Ibnu Daqiq Al ‘ied and translated by Muhammad Thalib. The data collection is done by taking the sample or called technique sampling. Technique of presenting data is presented by words and table of data to describe the analysis result. This reaserch investigates cohesion, variasion of translation technique, translation method, and ideological translation used by the translator in translating the expressions in the hadith.Keywords: hadith Arba’in, cohesion, technique, method, ideology.